KRISTUS LOGOS DAN TEOLOGI SEJARAH: PROLOGOUMENA UNIVERSALITAS KESELAMATAN - Aloysius Rusmadji (Kariwari: Jurnal Pendidikan Agama Katolik dan Pastoral, 2024)
a well known axiome extra ecclesiam nulla salus is frequently misintrepreted an exclusive meaning that only the member of the church will entertain salvation from Christ. Placed in historical context, the original formulation of the axiome is not intended so, that it is a task of the Church and theologians to study germs of the universality of the salvation Jesus Christ has brought to the world. Particular interpretation offered here is that of J. Dupuis who elaborated theological endeavours of Latin fathers: Augustine and Origens who presented Jesus enveloped in theology of history; and Greek Fathers: Justine, Ireneus, and Clemens who furnished Jesus Christ as Logos.